Financial crisis impact on the Lithuanian stock market - Bareikienė, Daiva; Sūdžius, Vytautas (Business: Theory and Practice, 2011)
The purpose of this article is to evaluate financial crisis impact on the Lithuanian stock market. Nowadays financial crisis of 2007–2010 is a very popular issue between society, government and financial institutions. Such an event changed everyone’s daily routine. Besides, this important and specific crisis affected goals, strategies and plans of many institutions. After this crunch lots of investors started to doubt about the reliability of stock market. For this reason, the factors which make impact on the Lithuanian stock market, are determined and the characteristics of the period of 2003–2010 in the Lithuanian stock market are presented. The method of the moving averages is used in order to analyze the dynamics of the stock market and to forecast the perspectives of the market. The results of the research showed that the financial crisis made the biggest negative impact on the Lithuanian stock market during the year 2008. Despite this, the market is slowly recovering and it is possible that it will start to develop in the near future. Article in Lithuanian. Finansų krizės poveikis Lietuvos vertybinių popierių rinkai Santrauka. Nagrinėjama Lietuvos vertybinių popierių rinkos būklės kitimo dėl susidariusios finansų krizės problema. Nustatomi Lietuvos vertybinių popierių rinkos ypatumai, veiksniai, darantys didelį poveikį OMXV indekso Santraukakitimui. Pateikiamos Lietuvos vertybinių popierių rinkos 2003–2010 m. charakteristikos, pritaikomas slankiųjų vidurkių metodas. Analizuojamas finansų krizės poveikis investuotojų nuomonei apie investavimą ir artimiausi investuotojų lūkesčiai. Remiantis atlikta apklausa ir OMXV indekso kitimo dinamika nustatomos investavimo perspektyvos. Tyrimas atskleidė, kad didžiausias neigiamas finansų krizės poveikis Lietuvos vertybinių popierių rinkai pasireiškė 2008 m., tačiau rinka iš lėto atsigauna ir tikėtina, kad artimoje ateityje Lietuvos vertybinių popierių rinka pradės sparčiai plėstis. Reikšminiai žodžiai: finansų krizė, vertybinių popierių rinka, slankiųjų vidurkių metodas, investavimas, OMXV indeksas, amplitudė.